简体   繁体   中英

Use foldr to define map in Haskell,

I'm new to Haskell and try to understand the map function.

I understand the following so far.

map::(a->b)->[a]->[b]
map f (x:xs) = f x : map f xs

But I don't understand following definition: Use foldr to define map

map'::(a->b)->[a]->[b]
map' f = foldr ( (:).f ) []

Can anyone explain the above map' definition and why it is same as map

Let's look at the source of foldr :

foldr k z = go where
    go []     = z
    go (x:xs) = k x (go xs)

Now let's compare the definition of map to the definition of go above:

map f []     = []
map f (x:xs) = f x : map f xs

It looks very similar, doesn't it? Let's rewrite the second clause to pull out the part that combines x with the recursive call's result:

map f []     = []
map f (x:xs) = (\v vs -> f v : vs) x (map f xs)

Now the parallel is very clear; we can even write some names to crystallize the parallel:

map f []     = z              where z = []
map f (x:xs) = k x (map f xs) where k = \v vs -> f v : vs

Just substitute go everywhere you see map f in the above and you'll see that the definitions are identical! So in the spirit of DRY, we can try to reuse foldr for the above:

map f = foldr (\v vs -> f v : vs) []

That gets you the big idea on how to get from map to foldr . Getting all the way to the definition you gave is then just some syntax tricks. We'll concentrate on the function argument to foldr now:

\v vs -> f v : vs
= { writing the infix operator prefix instead }
\v vs -> (:) (f v) vs
= { eta reduction }
\v -> (:) (f v)
= { definition of function composition }
\v -> ((:) . f) v
= { eta reduction }
(:) . f

So using this chain of reasoning, we can reach the final form

map f = foldr ((:) . f) []

An alternate answer, hopefully more accessible to some people.

foldr fz xs replaces every : in xs with f , and [] with z . So

 a : b : c : d : []

becomes

 a `f` b `f` c `f` d `f` z

Now let's substitute values from the definition of map' .

a `(:).f` b `(:).f` c `(:).f` d `(:).f` []

(I'm stretching the Haskell syntax a bit).

Now,

a `(:).f` as

is the same as

(:) (f a) as

which is the same as

f a : as

Continuing wit this transformation, we get

f a : f b : f c : f d : []

Hey, this looks like straight map f applied to [a,b,c,d] , doesn't it?

First you need to understand

foldr (:) []

the other one is just applying function f before cons, therefore equivalent to map

The technical post webpages of this site follow the CC BY-SA 4.0 protocol. If you need to reprint, please indicate the site URL or the original address.Any question please contact:yoyou2525@163.com.

 
粤ICP备18138465号  © 2020-2024 STACKOOM.COM